ESG, foreign ownership, and profitability on stock price volatility in mining and plantation companies - Suseno, Aan; Puspitasari, Intan; Ishak (E-Jurnal Akuntansi, 2026)
The effects of Environmental, Social, and Governance (ESG) performance, foreign institutional ownership, and profitability on stock price volatility in mining and plantation companies listed on the Indonesia Stock Exchange during the 2022–2024 period are analyzed in this study. Using panel data regression on 41 firms, stock price volatility is measured based on the standard deviation of daily returns, while ESG performance is proxied by the Katadata Corporate Sustainability Index (KCSI). The results show that variations in profitability and firm size are statistically significant affect stock price volatility, whereas ESG performance and foreign institutional ownership have no significant effect.